COMPARISON OF THE OUTCOME OF MONOPOLAR VERSUS BIPOLAR DIATHERMY USE DURING TRANSURETHRAL RESECTION OF PROSTATE - IMRAN , M; SHEIKH, MA; ALEEM, A; RASOOL, M; REHMAN, SU; IMRAN, MA (Biological and Clinical Sciences Research Journal, 2024)
Monopolar transurethral resection of the prostate (M-TURP) remains a widely used surgical modality for treating benign prostatic hyperplasia (BPH). However, bipolar TURP (B-TURP), which uses isotonic saline as an irrigant, may reduce the risk of dilutional hyponatremia and transurethral resection (TUR) syndrome associated with M-TURP. Objective: To compare the outcomes of bipolar versus monopolar diathermy during transurethral resection of the prostate. Methods: This randomized controlled trial was conducted at the Department of Urology & Renal Transplantation, Bahawal Victoria Hospital, Bahawalpur, from March 1, 2022, to May 31, 2023. The study included 100 patients, aged 55 to 85 years, scheduled for transurethral resection of the prostate due to BPH. Exclusion criteria were prostatic carcinoma, previous prostate surgery, cirrhosis, chronic renal failure, and bleeding disorders. Patients were randomized into Group A (M-TURP with 5% dextrose water as irrigant) and Group B (B-TURP with normal saline as irrigant). Outcomes, including changes in serum sodium levels, hemoglobin levels, and incidence of TUR syndrome, were assessed 12 hours postoperatively. Statistical analysis was performed using appropriate methods to compare the two groups. Results: The mean drop in hemoglobin (g/dL) was significantly more significant in the bipolar group (51.71 ± 7.28) compared to the monopolar group (47.86 ± 8.26) (p = 0.0001). The mean decrease in serum sodium levels (mEq/L) was significantly less in the monopolar group (143.57 ± 13.85) compared to the bipolar group (75.51 ± 7.98) (p = 0.0001). TUR syndrome occurred in 2 (4.0%) patients in the M-TURP group, whereas no cases were reported in the B-TURP group (p = 0.153). Conclusion: Bipolar transurethral resection of the prostate is associated with a smaller drop in hemoglobin, a lesser decrease in serum sodium levels, and a lower incidence of TUR syndrome than monopolar transurethral resection.